2022
DOI: 10.1111/obr.13446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise on waist circumference in adults with overweight or obesity: A systematic review and meta‐analysis

Abstract: Summary Excess visceral adiposity contributes to elevated cardiometabolic risk, and waist circumference is commonly used as a surrogate measure of visceral adipose tissue. Although regular aerobic exercise is known to improve abdominal obesity, its effect on waist circumference is unclear. A systematic review and meta‐analysis was performed to determine (1) the effect of aerobic exercise on waist circumference in adults with overweight or obesity; (2) the association between any change in waist circumference a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 137 publications
3
21
0
Order By: Relevance
“…Armstrong et al introduced the study's goal was cardiac exercise's influence on memory formation in people studied with moderate cognitive impairment (MCI) compared to no activity or any other intervention [31]. e research included in this review examined the effects of aerobic exercise on the brain-derived factor, brain architecture, or brain activity.…”
Section: Related Workmentioning
confidence: 99%
“…Armstrong et al introduced the study's goal was cardiac exercise's influence on memory formation in people studied with moderate cognitive impairment (MCI) compared to no activity or any other intervention [31]. e research included in this review examined the effects of aerobic exercise on the brain-derived factor, brain architecture, or brain activity.…”
Section: Related Workmentioning
confidence: 99%
“…Another study showed a dose response related to exercise intensity, such that the ability of exercise to reduce visceral adiposity appeared to be driven by exercise intensity. That is, vigorous intensity exercise induces greater reductions in waist circumference compared with moderate intensity [ 118 ], thus supporting the effectiveness of exercise to selectively target visceral fat in a dose-dependent manner.…”
Section: Exercise Improves Metabolic Health Following the Menopausementioning
confidence: 99%
“…Obesity is a threat to global population health in terms of prevalence and disease burden. In recent research, 2 billion people was diagnosed with overweight or obesity ( 2 ). In obese and overweight patients, the active metabolism of adipose tissue induces metabolic changes, such as increased production of reactive oxygen species, oxidative stress and inflammation, leading to type 2 diabetes mellitus (T2DM), arterial hypertension and dyslipidemia, which are the most important precursor risk factors for cardiovascular diseases (CVD) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%